Liver Enzyme Parameters in Patients with Breast Cancer: Pre- and PostRadiation therapy - Athraa Alkindi; Wisam Kadhum H. Alhashemi (Genius Journals, 2022)
Breast cancer (BC) is one of the most lethal and life-threatening cancers and is the most common among women worldwide; in general, it is the second most common type of cancer. Radiotherapy (RT) remains an essential component of cancer treatment. RT's main purpose is to stop cancer cells from multiplying (cell division potential). RT used for cancer treatment depends on the production of reactive oxygen species (ROS). The main impact of RT happens indirectly through the ionization of water molecules to ROS, such as superoxide and hydroxyl radicles in the cytoplasm. This follow-up 1:1 study aimed to investigate some biochemical parameters in BC patients before and after RT treatment compared to the healthy as a control group. In this study, (60) healthy female subjects served as a control group and a (60) patient females who had been followed up before and after RT treatment. All The participant patients will get RT treatment after being diagnosed with malignant BC, undergo surgery (mastectomy or lumpectomy), and finish the chemotherapy cycles. Levels of Liver enzymes (alkaline phosphatase (ALP), alanine Transaminase (ALT) and aspartate transaminase (AST)) were all analyzed in patients and healthy controls. In the present study, the results will illustrate in three parts; Part one: a comparison between cancer patients before RT )G2) and healthy subjects as a control group (G1); the (ALP, ALT, and AST) concentrations levels were significantly higher in G2 compared to G1 (p <0.05). Part two: comparison between cancer patients after RT (G3) and healthy as a control group (G1); the (ALP, ALT, and AST) concentrations levels were significantly higher in G3 compared to G1 (p><0.05). Part three: comparison between cancer patients before (G2) and after (G3) RT; the (AST, ALT, and ALP) levels there was no difference between G3 and G2. In the present study, Patients with BC treatment methods are in a condition of high oxidative stress, necessitating antioxidant supplements>
Keywords: Radiotherapy; Liver enzymes; breast cancer; ALT